Determinant factors related to female adolescents' attitudes toward gender-based violence - Rr Dian Tristiana; Ika Nur Pratiwi; Ah Yusuf; R Endro Sulistyono (Healthcare in Low-resource Settings)
The prevalence of violence, especially against female adolescents and children, is still quite high. This study aimed to analyze the factors that influence female adolescents’ attitudes toward gender-based violence. We employed a cross-sectional research design, and the study population consisted of 107 adolescents in Surabaya who accessed the Google form. The statistical analysis used the chi-square test for the adolescent's characteristics and Spearman's rank correlation with α=0.05. The study found a significant correlation (p<0.005) between adolescents' attitudes toward gender-based violence and their father and mother's education levels. Additionally, school climate (p<0.005) and family conflict (p<0.005) also correlated with these attitudes. Adolescents' formative years are primarily centered around their homes and schools, making these environments crucial for shaping their beliefs and actions. Therefore, they present valuable opportunities for educating young people about gender-based violence. The research emphasizes the need for comprehensive changes in teenagers' attitudes, calling for active participation from teenagers themselves, their families, schools, society, and social media regulations.